PJMHS 2022
DOI: 10.53350/pjmhs22162959
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Percutaneous Peritoneal Drainage in High Risk Perforated Peritonitis

Abstract: Study Design: Prospective study Place and Duration: The study is conducted at Surgical A ward Mardan Medical Complex, Mardan and Surgery department of Ahmed Hospital, Bagh Azad Kashmir during the period from June to November 2021. Methods: There were 85 patients of both genders with ages 22-80 years included. Patients were included into the study after obtaining written permission from all participants. All the patients had high perforation peritonitis treated with percutaneous peritoneal drainage with local a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The mortality rate was found to be 65.2%. This is in contrast with majority of the studies, which have observed a lower death rate in patients undergoing percutaneous peritoneal drainage 16,17,18,19 . Only a few studies have comparable results with our research 14,20 .…”
Section: Discussionmentioning
confidence: 57%
“…The mortality rate was found to be 65.2%. This is in contrast with majority of the studies, which have observed a lower death rate in patients undergoing percutaneous peritoneal drainage 16,17,18,19 . Only a few studies have comparable results with our research 14,20 .…”
Section: Discussionmentioning
confidence: 57%